(untitled) (Editora Impacto Científico, 2025)
The objective was to investigate the level of knowledge of cockatiel owners regarding measures to control parasitic diseases. A questionnaire was applied in the form of an interview, consisting of closed questions about the management practices adopted by 50 owners of these pets, residing in the urban area of ​​the Municipality of Araçatuba, São Paulo. From the information obtained, it was observed that most of the birds were acquired from breeders without deworming and did not present diarrhea. Also, 52% of the owners cleaned the cages daily and 48% weekly, with 96% not using gloves and masks for this procedure. It is important to mention that 86.8% of the cockatiels consume tap water. Thus, it can be concluded that the owners have basic knowledge of the correct management to be given to their birds, but they should be correctly instructed on the deworming protocol for cockatiels and regarding the use of protective equipment when handling the fecal material of their birds. DOI: https://doi.org/10.56238/edimpacto2025.090-064